Therapeutic Hypothermia after Prolonged Cardiac Arrest: Case Report with Review of Literature - Gautam Rawal; Sankalp Yadav; Nitin Garg (Journal of Clinical and Diagnostic Research, 2015)
Patients who survive cardiac arrest often develop severe neurological dysfunction due to the hypoxic brain injury and reperfusion induced cell death. Therapeutic hypothermia (TH) has become a standard therapy of cerebral protection following the successful return of spontaneous circulation in patients of out-of-hospital cardiac arrest, according to American heart association guidelines. This is a case report of a 30-year-old patient who developed in-hospital cardiac arrest and was revived after prolonged cardiopulmonary resuscitation (CPR) and also required primary angioplasty. TH was then established with local measures for 24 hours for cerebral protection. The patient was gradually and successfully weaned off from ventilator with no neurological impairment. There is an increasing evidence of TH and its protective mechanisms in patients with non-shockable arrest rhythms with particular emphasis on neurological outcomes. This article emphasizes the role of TH in every successful CPR irrespective of the cardiac rhythm.